Non-Hodgkin's B-cell lymphoma of the ovary: A case report and review of the literature - Yu-Wen Sung; Yun-Shan Lin; Yen-Ting Chen; Lian-Shung Yeh (Elsevier, 2022)
Objective: To report a case and review published cases of non-Hodgkin's lymphoma of the ovary. Case report: A 30-year-old female presented with abdominal fullness. Abdominal CT revealed bilateral huge ovarian masses with moderate amount of ascites. Explore laparotomy was performed and the frozen section of right ovarian mass reported to be malignant lymphoma. The final diagnosis was Ann Arbor stage IV diffuse large B cell lymphoma. The patient received six cycles of chemotherapy with RCHOP regimen. She achieved complete remission after the treatment, and there's no evidence of recurrence after 12 months follow up. Conclusion: Ovarian lymphoma is a rare condition. It could present with findings mimicking ovarian cancer. Chemotherapy is the main treatment option and cytoreductive surgery should be avoided.